2021
DOI: 10.1590/1414-431x202010118
|View full text |Cite
|
Sign up to set email alerts
|

Uterine vascular resistance and other maternal factors associated with the risk of developing hypertension during pregnancy

Abstract: Gestational hypertension and pre-eclampsia are important causes of perinatal morbidity. The objective of the present study was to determine the increase in relative risk for developing hypertensive disorders of pregnancy based on the evaluation of pregnant women between 20 and 25 weeks of gestation, and to correlate the findings at this period with the outcome of pregnancy. We conducted a prospective cohort study, with a convenience sample of 1417 patients evaluated at this gestational age, of which 1306 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…Extensive research has led to the identifying several potential biomarkers for the detection of preeclampsia 63 , 64 , 65 , 66 ; however, their sensitivity and specificity for early detection are low. 67 It has recently been shown that development of PE is associated with increased levels of e Hsp‐70, e Hsp‐90 and TNFα in blood and plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive research has led to the identifying several potential biomarkers for the detection of preeclampsia 63 , 64 , 65 , 66 ; however, their sensitivity and specificity for early detection are low. 67 It has recently been shown that development of PE is associated with increased levels of e Hsp‐70, e Hsp‐90 and TNFα in blood and plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our current study, gestational age related to the marked decline in umbilical artery PI has been reported [53], which reflects placental villous circulation.in addition; there was an inverse relation ship between both doppler indices and blood flow velocity [53][54][55][56], Moreover, Wladimiroff et al [57] calculated mean RI values at different gestational ages among normal pregnant women. Therefore, noninvasive color and pulsed wave Doppler sonography have been used to evaluate uterine and umbilical blood flow changes during normal pregnancy during different gestational months at different ages, as the changes in these two parameters provide a picture of intrauterine fetal development, as previously mentioned in pregnant buffalos [58,59], sheep [60], queens [61], and bitchs [62]. The use of Doppler spectral ultrasound in gestational observation in donkey species is recommended to prevent any pregnancy loss and abnormal placental development, with the estimation of uterine and umbilical vascularity.…”
Section: Discussionmentioning
confidence: 99%
“…18 anos. Da amostra total, 71.8% tinham atividade exclusivamente no lar, a maioria, 31.8% viviam sem salário, 18.2% com até um salário-mínimo, 85.4% eram casadas ou com relação estável e 84.5% se consideravam parda.…”
unclassified